A high–temperature Mohr–Coulomb criterion dependent on temperature, strain rate, and stress state for ductile fracture prediction. (January 2022) - Li, Haijun; Li, Tianxiang; Ning, Xinyu; Li, Ruihao; Wang, Zhaodong
Abstract: The cracks formed in the hot deformation are typical defects caused by plastic capacity limitations. For tested steels, the fracture behavior is associated with temperature, strain rate, and stress state. In this study, a highly crack-sensitive steel with Nb micro-alloying is selected as the research material to establish the fracture criterion considering the above factors comprehensively. First, compression and tension experiments are performed, and various specimen geometries are designed to produce different stress states in the tests at different temperatures and strain rates. Second, the critical stroke of these tests is extracted, and corresponding calculations are completed using the finite element method (FEM). The loading paths of stress states are independent of temperature and strain rate; however, they differ when distinct specimen shapes are considered in the tests. Third, a high–temperature Mohr–Coulomb criterion, which is applicable at elevated temperatures, is established by considering the effects of temperature, strain rate, and stress states on fracture. Finally, some examples of compressive and tensile tests are employed for verifying the formulated fracture criterion. By comparing the FEM and experimental results, it is found that the fracture criterion could accurately describe the fracture behavior during hot deformation with distinct stress paths. Highlights: Various stress states and stress paths are used in the tests for modeling at elevated temperatures. In-situ observation of fracture based on CLSM. A modified Mohr–Coulomb criterion is established by considering the influences of stress state, temperature, and strain rate. Fracture analysis and model validation are accomplished based on the combined experimental and FEM results.